Kemampuan Kepemimpinan Klinis Perawat Pelaksana Berdasarkan Pendekatan Clinical Leadership Competency Framework dan Faktor-Faktor Determinannya - Yusnaini Yusnaini; Yulastri Arif; Dorisnita Dorisnita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze nurses' clinical leadership abilities based on the clinical leadership competency framework approach and its determinants in the inpatient room of Padangsidimpuan Hospital. The research design in this study used a descriptive-analytic correlation. The results showed that there was a significant relationship between the availability of nursing resources, management support, and work environment support with clinical leadership abilities, with a p-value for each variable, namely the availability of nurse resources (p = 0.043), management support (p = 0.000) and support work environment (p = 0.005). Meanwhile, competence has no significant relationship with nurses' clinical leadership ability in the inpatient room of RSUD Padangsidimpuan (p = 0.084). Multivariate analysis shows that management support is the most dominant variable associated with clinical leadership skills, with an Odds Ratio (OR) value of 4.476. In conclusion, nurses' clinical leadership ability must be supported by the availability of nurse resources, work environment support, and management support to obtain quality nursing services. Keywords: Determinants, Respondent Characteristics, Clinical Leadership